KAWASAN WISATA AIR TERJUN DAIT DI KABUPATEN LANDAK - Windi Guswirno Hedi; Syaiful Muazir; Valentinus Pebriano (JMARS: Jurnal Mosaik Arsitektur, 2021)
Landak Regency has many natural resources that have the potential to be used as natural tourism objects. One of them is Dait Waterfall which has 7 floors and is located in an unspoiled forest area. The area is often visited by tourists from various regions of West Kalimantan. However, there are several problems related to supporting facilities and infrastructure that are not up to standard for tourism activities, so that the tourism potential is not maximized. For this reason, it is necessary to design a "Dait Waterfall Tourism Area in Landak Regency" which is in accordance with tourism standards and local environmental needs, with the concept of ecotourism that uses a sustainable environmental approach and empowerment of local communities. The arrangement is done by designing which starts from the function analysis process, which includes the main functions and supporting functions. The main functions include recreational aspects and supporting functions consisting of commercial functions, ecological functions and community participation functions. The design method consists of the introduction, definition, preparation, analysis, synthesis, evaluation and re-evaluation stages. The design process is applied in the construction of the main tourism facilities and infrastructure such as outbound areas, camping areas, selfie areas, and others. In addition, supporting facilities and infrastructure such as management areas, commercial areas, service areas, utility aspects, and others. With this design, it is hoped that the Dait Waterfall Tourism Area will attract more tourists from a wider variety of areas.